Shaft [videorecording (DVD)] - Story, Tim; Jackson, Samuel L; Usher, Jessie T.; Hall, Regina (Warner Bros. Entertainment, 2019)
With the help of his family, JJ Shaft tries to unveil the truth behind his friend's unexpected death.